Prolonged Late Mesoproterozoic to Late Triassic Tectonic Evolution of the Major Paleo-Asian Ocean in the Beishan Orogen (NW China) in the Southern Altaids - Qigui Mao (Frontiers in Earth Science, 2022)
The accretionary processes and the continental growth of the Altaids are still controversial. The Beishan orogen is situated in the southernmost Altaids and is an ideal tectonic site to address these issues. In this study, we report the results of new field-based lithological mapping and structural analysis on the Huaniushan complex in the Beishan orogen, which is composed of blocks of serpentinized ultramafic, gabbro, basalt, chert, limestone, and other rocks within a strongly deformed and cleaved matrix of sandstone and schist. Our new zircon U-Pb date reveal that a gabbro block formed at 504 ± 3 Ma. Our geochemical and isotopic data of gabbroic and basaltic blocks show that they are relics of the Mid-Ocean-Ridge (MORB)-type and Ocean-Island-Basalt (OIB)-type oceanic lithosphere, with high values of εNd(t) (+4.3–+14.5) and εHf(t) (+8.07–+17.74). The maximum depositional ages (MDAs) of two sandstone blocks were dated at 309 ± 5 Ma and 502 ± 11 Ma, respectively. U-Pb ages and Hf isotopes of detrital zircons from the matrix sandstones indicate that they were derived only from the Shuangyingshan–Huaniushan arc to the north. Accordingly, the Huaniushan complex was part of the Liuyuan accretionary complex that fringed the Huaniushan arc, and, therefore, formed by the northward subduction of the Liuyuan oceanic plate. Combined with the basalt yields zircon U-Pb age of 1,071 ± 5 Ma, we concluded that the Huaniushan complex has an age of 1,071 Ma to 309 Ma. Furthermore, the oceanic blocks and sedimentary matrix of the Liuyuan accretionary complex have an age of 1,071–270 Ma and 920–234 Ma, respectively, suggesting that the Liuyuan Ocean was still open at ca. 234 Ma. Thus, the studies reveal that the Liuyuan Ocean, a major branch of the Paleo-Asian Ocean, may have experienced a prolonged tectonic history, starting in the late Mesoproterozoic (1,071 Ma) and terminating later than the late Triassic (234 Ma), with a long subduction and development of a series of seamounts and/or plateaus emplaced into the Liuyuan accretionary complex.